Issues of Sukuk Ijarah - Faiza Husnayeni Nahar; Mufti Alam Adha; Dyah Titis Kusuma Wardani (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2018)
Sukuk Ijarah is the most popular sukuk that increase in over the world since its start to introduce in 2001. Not only Muslim country who issued this sukuk, so do Non-Muslim Country such as Germany, Japan and China. However, there is issue that come up due to the non-existence of Shariah compliance in this structure such as the requirement of sukuk doesn’t meet Maqasid Shari’ah perspective. Therefore, the aims of this paper to discuss some issue in sukuk Ijarah and give solution in order to develop Islamic capital market.